An Albumin-Glutaraldehyde Nanoparticle Loaded with Berberine Inhibits Cell Growth and Induces Apoptosis in Colon Cancer HCT-116 Cells - Munusamy, Murugan Alwarkurichi; Bharathi, Muruganantham; Alarfaj, Abdullah A.; Hussein-Al-Ali, Samer Hasan; Sarathbabu, Subbarayan; Nagaiya, Ravichandran (Indian Journal of Pharmaceutical Education and Research, 2025)
Background The study aims to synthesize and characterize berberine-loaded albumin-glutaraldehyde nanoparticles and evaluate their anticancer activity against colon cancer HCT-116 cells. The research focuses on the mechanisms involved in oxidative stress-dependent apoptosis, crucial for inhibiting colon cancer growth and promoting overall health. Materials and Methods The synthesized Berberine-Albumin NPs were characterized using several techniques, including UV-visible spectroscopy, X-ray Diffractometer (XRD), Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), Fourier Transform Infrared (FT-IR), Dynamic Light Scattering (DLS) and Photoluminescence (PL) studies. The antibacterial potentials of Berberine-Albumin NPs against various pathogens were examined using the well diffusion technique. The cytotoxicity of Berberine-Albumin NPs against HCT-116 cells was evaluated using the MTT assay. The study evaluated ROS production and apoptosis in HCT-116 cells treated with Berberine-Albumin NPs using fluorescence staining and oxidative stress marker levels using assay kits. Results The characterization analyses revealed the presence of Berberine-Albumin NPs with a cuboidal shape and an average particle size of 155.80 nm. Several elements and functional groups in Berberine-Albumin NPs were also identified. The synthesized Berberine-Albumin NPs exhibited remarkable antimicrobial properties by efficiently suppressing the growth of several pathogens. The treatment with Berberine-Albumin NPs effectively suppressed the proliferation of HCT-116 cells. The findings of fluorescence staining experiments confirmed more ROS accumulation and apoptosis in HCT-116 cells treated with Berberine-Albumin NPs. The administration of Berberine-Albumin NPs resulted in an upregulation of oxidative stress in HCT-116 cells. Conclusion In summary, this work revealed that synthesized Berberine-Albumin NPs had anticancer effects against colon cancer. Hence, the present findings indicate that Berberine-Albumin NPs hold promise as an effective candidate for colon cancer treatment. In future studies, we would like to evaluate clinical relevance, comparative analysis, long-term effects and biodistribution and pharmacokinetics of Berberine-Albumin NPs.
Keywords: Nanoparticles; Berberine; Albumin; Colon cancer; Oxidative stress; Apoptosis.